2021
DOI: 10.2147/rmhp.s294885
|View full text |Cite
|
Sign up to set email alerts
|

Risk Communication Effectiveness During COVID-19 Pandemic Among General Population in Saudi Arabia

Abstract: Purpose The novel coronavirus (COVID-19), declared a pandemic by WHO in March 2020, is an unprecedented occurrence in our recent history. Effective risk communication by health authorities, through relaying reliable and authoritative information, is imperative in combating the spread of the outbreak. We aimed to measure the effectiveness of risk communication campaign and overall awareness during COVID-19 pandemic among the general population in Saudi Arabia. Patients and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…During the COVID-19 pandemic, the highest Saudi authority responsible for credible information is the MOH. 15 Our study shows that traditional media like television, radio, and newspapers, although used by the MOH for health messaging before and during the pandemic, the caregivers did not turn to traditional media for health advice. This could be because the caregivers’ age group (young adult aged 18–35 years) tends to seek more information online, 16 and the electronic format of the survey can result in a sampling bias.…”
Section: Discussionmentioning
confidence: 65%
“…During the COVID-19 pandemic, the highest Saudi authority responsible for credible information is the MOH. 15 Our study shows that traditional media like television, radio, and newspapers, although used by the MOH for health messaging before and during the pandemic, the caregivers did not turn to traditional media for health advice. This could be because the caregivers’ age group (young adult aged 18–35 years) tends to seek more information online, 16 and the electronic format of the survey can result in a sampling bias.…”
Section: Discussionmentioning
confidence: 65%
“…Twitter, the most widely used social media network, followed by WhatsApp and other social media platforms used by the public, 14 was utilized by government officials and concerned institutions to reach the populace by broadcasting daily updates on confirmed cases, fatalities, and recoveries. Social media were also used to spread health awareness, educational messages, and visual infographics to keep the public informed on current precautionary measures and encourage individuals to follow government instructions.…”
Section: Resultsmentioning
confidence: 99%
“…The use of digital technology in the eight pillars of response is vital for the function and success of each respective area of preparedness and response. [13][14][15] These technologies have been adapted worldwide to perform multiple tasks related to the pandemic, including prevention and such surveillance as contact tracing. 12 Moreover, these different technologies had several benefits, including 35 separate beneficial effects that improved patients' outcomes and decreased the impact of the outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…And another study showed that the most common source of information for COVID-19 in Saudi Arabia were official government social media, and Twitter [48] . Other sources of getting information regarding COVID-19 in Saudi Arabia includes text messages, television, and the official Saudi MOH call center (the 937 number) [49] . Other studies also showed dependence on the Saudi and US Centers for Disease control and preventions [50] , or the official websites of the Saudi MOH and the World Health Organization (WHO) [51] .…”
Section: Discussionmentioning
confidence: 99%